Parental Parenting Patterns Toward Children with Disabilities in the Inclusive School Raudhatul Athfal Ulumul Quran Al Madani Banjarbaru - Hanifa Muthaharah; Hermanto Hermanto; Anisa Sri Rizky; Cindy Rahmi Aulia; Monika Nur Edlina (Journal of Educational Sciences, 2026)
Parenting children with disabilities requires adaptive strategies that address their unique developmental and emotional needs. However, variations in parenting practices are often overlooked, particularly in understanding how core parenting dimensions are applied in real contexts. This study aims to provide an in-depth description of parenting styles and their key aspects warmth, control, and communication among parents of children with disabilities. This research employs a qualitative approach with a descriptive multiple case study design. Informants were selected purposively, consisting of four parents of children with disabilities, one special education teacher, and one individual from the parents’ social environment. Data were collected through in-depth interviews, observations, and documentation, and analyzed through cross-case comparison. The findings indicate that parenting practices generally reflect a democratic pattern. However, the implementation of warmth, control, and communication varies across cases and is adapted to the child’s specific condition. In addition, parents face several challenges, including limited knowledge and skills, difficulties in supporting children’s developmental tasks, and constraints related to the child’s condition. In conclusion, parenting in this context is dynamic and context-dependent, highlighting the need for increased parental support and practical guidance.